Separate Civil Cases in Bankruptcy Proceedings - Markosyan, Tigran (Bulletin of Yerevan University C: Jurisprudence, 2022)
The institute of separate civil cases in bankruptcy proceedings is a novelty in domestic legislation and its comprehensive study has great theoretical and practical significance.Based on theoretical sources, domestic and foreign legislation, as well as judicial practice, the article considers the need to introduce a separate institution of civil cases and the history of its development, analyzes the conditions for considering a civil dispute as a separate civil case and other elements of this institution, and also identifies the limits of the moratorium on civil cases.In the article, the author has introduced several scientific-practical conclusions that can be guiding for the development of law enforcement practice, as well as for further legislative development of the institute of individual civil cases.
Keywords: bankruptcy proceedings; moratorium; separate civil case; concentration; dispute over jurisdiction